DEVELOPMENT OF INTEGRATED AUDIO VISUAL MODULE FOR LEARNING ANIMATION PRINCIPLES AT MULTIMEDIA VOCATIONAL SCHOOL - Febri Dwi Prasasti; Robinson Situmorang; Dwi Kusumawardani (Peneliti.net, 2018)
Vocational High School aims to produce graduates who have certain skills so that they can improve their quality of life. One of the important competency to be mastered is in 2 Dimensional Animation Engineering subjects in multimedia Vocational School is the application of the principles of animation. The principle of animation will deliver the audience to be able to understand and enjoy an animated product. Competence in applying the principle of animation is important to be owned by vocational students majoring in multimedia, but in 2016 the results of practical tests showed that only about 25% of students achieved minimal completeness in the competence of applying the principle of animation. The lack of practical learning materials in applying the principles of animation and lack of learning hours in school are some of the problems that exist in the animation learning lack of student competence. The results of interviews with teachers showed that the teaching materials available were insufficient for teaching needs, so they felt the need for additional teaching materials. The three animation teachers hoped for an integrated learning module with audio visual to support the learning process in the classroom. The researcher intends to provide solutions to problems by developing learning resources in the form of learning modules that are integrated with audio-visual media, which will be used as material for learning carried out by teachers in the classroom. Audio visual modules and media were developed with Lee and Owen's multimedia development methods, namely through a series of stages starting from needs analysis, final preliminary analysis, design, development, implementation and evaluation. The results of the effectiveness test from the use of integrated audio visual media modules by 30 students, showed a significant increase based on the results of the t-test with a significance level of 5%